Follicular pityriasis rosea. A case report and a new classification of clinical variants of the disease. - Zawar, Vijay (Specjalisci Dermatolodzy, 2012)
BACKGROUND: Atypical forms of pityriasis rosea are often noticed in Indian children. MAIN OBSERVATIONS: We describe a 9-year-old male child with predominant follicular eruptions on trunk consistent with a clinical diagnosis of pityriasis rosea. CONCLUSION: Follicular pityriasis rosea is an extremely rare presentation of the disease. We propose a new classification of clinical variants of pityriasis rosea.